PELAKSANAAN PERDA NOMOR 10 TAHUN 2006 TENTANG SUMBER DAYA AIR DAN SUMUR RESAPAN(STUDI PADA DEPOT AIR MINUM DI KELURAHAN SIDOMULYO TIMUR) - GAMELDO YULINDRA; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The study is titled Implementation of Pekanbaru City Regulation No. 10 of 2006 Section 18 On Obligations Making Infiltration wells in East Sidomulyo . This study aimed to determine the implementation of the regulation -making depot absorption wells by drinking water that is in the East Village Sidomulyo . Policy theory , implementation , and monitoring is a cornerstone in the study . In terms of data collection techniques the author uses interviews with people who have the information and involvement in Pekanbaru City Regulation No. 10 of 2006 Section 18 On Obligations Making Infiltration wells in East Sidomulyo . The method used in this research is descriptive method of analysis with a qualitative approach that seeks to analyze the problems that arise in the field and tried to describe it well.According to Law No 7/2004 on Water Resources , water resources management is an effort to plan , implement, monitor , and evaluate the implementation of the conservation of water resources , efficient use of water resources , and control of the destructive force of water . With reference to the Law No. . 7/2004 of the Pekanbaru city government issued a regulation in 2006 at number 10 on the Utilization of Water Resources and Infiltration wells . It is intended to comply with the Act and at the same time keeping the water availability in the future . In Article 18, discussed about the obligation for employers to make water absorption wells or building certain criteria .Based on the results of the study authors , explained first , that the Government has implemented socialized Pekanbaru , emphasis and oversight by both the city of Pekanbaru ckup No. 10 of 2006, Article 18 . Second , implementation of Pekanbaru No. 10 of 2006 Section 18 in East Sidomulyo generous nature has been running quite well , although there are still those who do not comply with the regulation . Disobedience is due to the persistence of understandings of society that considers water resources will not be exhausted until whenever , and they feel the government is too busy with emphasis on the rules in almost every field . But this understanding of just a handful of people who need to be given further explanation by the local government or the government of Pekanbaru .Keywords: policy, implementation, and monitoring